Factors influencing personal saving in Thailand / Nurul Fathiyah Ghazali (Faculty of Business and Management, 2008)
Personal saving is the portion of personal income that is left over after personal current taxes and outlays for personal consumption expenditures, non mortgage interest payments, and net current transfers to government and the rest of the world. It excludes capital gains because capital gains represent changes in the prices of assets that are already owned, not unspent portions of income receipts. Personal saving represents the contribution from persons to national saving, which is the total amount that is available to fund investment in fixed assets, inventories, or foreign assets. This paper empirically analyzes the Factors Influencing Personal Saving in Thailand. The data are collected from Malaysia Economic Report, Bank Negara, Bank of Thailand, International Financial Statistics, Bursa Malaysia and Valuation and Services Department. The study used multiple regression analysis to see the relationships between dependant and independent variables. Personal saving was used as dependant variable and stock return, home ownership, and disposable income as independent variables. From the analysis that has been done, there is sufficient evidence to conclude that there is a relationship between disposable income, home ownership and stock return with personal saving in Thailand.